Vicarious Liability Theory on Vicarious Liability on Artificial Intelligence (AI) in the context of Cryptocurrency - Ayu Pramachanti Rumiartha; Timotius Nico Yogatama (Focus Journal : Law Review, 2024)
This study aims to discuss and analyze how substitute accountability in Artificial Intelligence (AI) in the context of Cryptocurrency, analyzed with Vicarious Liability theory. The use of Artificial Intelligence is also often used in the business of digital money transactions, for example such as cryptocurrency. Technological developments have given birth to various kinds of alternative tools or instruments as a substitute for money, which could be possible for violations of the law in the use of Artificial Intelligence (AI) in cryptocurrency transactions. The research method used in this study is a type of normative legal research method. In normative legal research, a study that leads to the process of finding legal rules, legal principles, and legal doctrines that function to answer legal issues faced. The choice of the type of normative legal research in this study is related to the analysis of Vicarious Liability Theory in the context of substitute liability in Artificial Intelligence (AI). The results of the study show the importance of understanding the theory of Vicarious Liability as a theory that determines substitute liability in Artificial Intelligence (AI), this is because the use of Artificial Intelligence is also often used in the business of digital money transactions, for example such as cryptocurrency, so it does not rule out the possibility that the AI does not carry out actions in accordance with AI commands which will certainly harm all parties, including business consumers of digital financial transactions in the event of a digital transaction error, then the person responsible is not the AI subject but the subject who from the beginning provides the use of Artificial Intelligence (AI) in cryptocurrency transactions.